Self-Phased Learning for Reducing Teachers’ Learning Loss with Guru Binar - Kisno Kisno; Catur Tina Anggraeni; Rita M. Siregar; Lidia Apriliana Nainggolan (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2022)
Most of educational activities has been interrupted by the existence of Covid-19 pandemic. An alternative in online learning such as Massive Open Online Courses (MOOC) came up as the temporary solution. Despite their existence, MOOCs did not warrant the successful online learning. Both teachers and students experienced learning loss during the pandemic situation and this phenomenon was undeniable. The aim of this paper is to investigate how Guru Binar as one of the MOOCs succeeded in reducing teachers’ learning loss. This paper implemented qualitative method and a structured-interview was carried out to the selected participants of Guru Binar users in Indonesia from primary and secondary schools. Three focus group discussions were held and eight Guru Binar participated in this research. It was found that Guru Binar was successful in reducing teachers’ time loss via interactive talkshow and webinar and the online classes helped users spend qualified time with innovative games. To sum up, a platform like Guru Binar was successful in diminishing learning loss and was recommended for the in-service teachers and prospective teachers for continuous professional development.